PENGARUH EFIKASI DIRI, KEPEMIMPINAN, MOTIVASI DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU SENAPELAN - Fauziah Rahmi (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The problem in this research is: Does the self-efficacy, leadership, motivation and work facilities partially and simultaneously affect the performance of Pekanbaru Senapelan Primary Service Office employees? Research Objectives: To find out whether self-efficacy, leadership, motivation and work facilities partially and simultaneously simultaneously affect the performance of Pekanbaru Senapelan Tax Office. The hypothesis proposed is: There is an effect of self-efficacy, leadership, motivation and work facilities partially and jointly on the performance of Pekanbaru Primary Tax Service Office Senapelan Research conducted at the Pekanbaru Primary Tax Office Senapelan Jalan Sudirman Number 247 Simpang Empat Pekanbaru , with a population of 110 people, and a sample of 86 people.Based on the analysis results obtained there is a significant effect between self-efficacy on the performance of the Pelanbaru Senapelan Tax Office employee, because according to the results of the analysis of t count t-table (3.159 1.67) at n = 93 with a significance level of 95%. There is a significant influence between leadership on the performance of Pelanbaru Senapelan Tax Office employees, the results of t-analysis t-table (2,439 1.67) at n = 93 with a significance level of 95%. There is a significant influence between work motivation towards the performance of the Pelanbaru Senapelan Primary Tax Office employee, because according to the results of the analysis of t count t-table (1.762 1.67) at n = 58 with a significance level of 95%. There is a significant influence between work facilities on the performance of the employees of the Senapelan Pelanbaru Tax Office, because according to the analysis of tcount t-table (3.897 1.67) at n = 93 with a significance level of 95%. F-count value F table (178.340 2.46) together (multiple) there is a positive and significant influence of self-efficacy, leadership, motivation and work facilities on the performance of employees of the Pelanbaru Senapelan Tax Office. Thus the hypothesis proposed is accepted